TREATMENT OF ORAL MUCOSAL LESIONS BY SCALPEL EXCISION AND PLATELET-RICH FIBRINMEMBRANE GRAFTING: A case report - Ivan Chenchev; Radka Cholakova (Journal of IMAB, 2016)
Purpose: The treatment of oral mucosal lesions and mucosal hypertrophy in particular, is most often achieved by an excision with or without covering the surface of the wound. The platelet rich fibrin membrane (PRFm) is an autogenous product containing platelets and leukocytes and their secreted growth factors and cytokines. The purpose of the presented clinical case is to describe a new, recent technique used for the covering of mucosal wounds left after the removal of pathological lesions. Material and Methods: On a single patient mucosal hypertrophy was removed by an excision with scalpel and the resulting surgical wound was covered with an autogenous PRF membrane. Postoperatively the healing process was followed on the 7th, 14th and 30th day. Results: The healing period went smoothly with minimal postoperative discomfort and no complications. Conclusion: The results of the presented clinical case demonstrate that the PRF membrane can successfully be used to cover postoperative mucosal defects.